Emergency nursing made incredibly easy! - Edwards, Mark; Griffiths, Pauline , 1951- (Wolters Kluwer/Lippincott Williams & Wilkins, 2011)
"One key step in emergency nursing is to quickly assess the patient's chief complaint, and act if necessary. Emergency Nursing Made Incredibly Easy will help the nurse hone these vital skills. This book covers the basics of triage, such as the evidence-based triage process, and holistic care issues, such as cultural and pain considerations. Subsequent chapters focus on physiological systems, covering neurologic, cardiac, respiratory, gastrointestinal, and musculoskeletal emergencies. It also discusses wound care management, genitourinary and gynecologic emergencies, maxillofacial and ocular emergencies, shock and multisystem trauma, and environmental emergencies. Emergency Nursing Made Incredibly Easy addresses the challenge of switching into "disaster mode," providing concise guidelines on mobilization and management for nurses facing natural and manmade events that cause mass-casualty incidents. The clear language and illustrations will help readers anticipate and assess certain diagnoses, and prevent predictable complications. Recurring topics for each section include how to assess the patient, diagnostic tests that should be done, treatment options, and common disorders for each body system. A Quick quiz at the end of each chapter tests the reader's knowledge on the information presented"--Provided by publisher